Representasi Mental Ambiguitas Semantik Pada Teks Naratif dan Implikasinya Terhadap Pemahaman Bacaan di Kalangan Remaja - Nur Syavika; Wiji Rahayu; Fatmawati F (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study analyzes adolescents' mental representations of semantic ambiguity in narrative texts and their implications on reading comprehension through a descriptive qualitative approach. Literature studies are the main data collection technique from books and scientific journals related to semantic ambiguity, mental representation, narrative texts, and adolescent reading comprehension. Data analysis involves information reduction, narrative presentation, and drawing conclusions to illustrate the relationship between linguistic phenomena and readers' cognitive processes. Lexical ambiguities in the form of polysemimes and homonyms, syntactic ambiguities of double sentence structures, and ambiguities of slang or cultural meanings result in unstable mental representations that require language decoding, inference, meaning revision, and continuous monitoring of understanding. This cognitive process increases the workload of working memory so that adolescents' reading comprehension varies, decreases the accuracy of interpretation of storylines, characters, and main messages, although it also trains critical thinking if successfully completed effectively.